Effects of some heavy metals on content of chlorophyll, proline and some antioxidant chemicals in bean (Phaseolus vulgaris L.) seedlings - Zengin, FK; Munzuroglu, O (Polska Akad Nauk, Polish Acad Sciences, Pas Branch Cracow, 2005)
The effects of lead, copper, cadmium and mercury on the content of chlorophyll, proline, retinol, alpha-tocopherol and ascorbic acid were investigated in 17-day-old bean seedlings (Phaseolus vulgaris L.) grown in Hoagland solution spiked with various concentrations of Pb, Cu, Cd and Hg. Control and heavy metal-treated plants were grown for 10 days in Hoagland solution. Content of total chlorophyll (a and b), proline, retinol, alpha-tocopherol and ascorbic acid was measured in ten-day-old primary leaves by High Performance Liquid Chromatography (HPLC). Total chlorophyll content declined progressively with increasing concentrations of heavy metals. A significant increase of proline, retinol, alpha-tocopherol and ascorbic acid content was detected in primary leaves after ten-day exposure to heavy metals. The strongest effect on total chlorophyll, proline, retinol, alpha-tocopherol and ascorbic acid content was found in plants exposed to mercury, followed by the sequence Cd++ > Cu++ > Pb++.
Keywords: chlorophyll; heavy metal; proline; retinol; alpha-tocopherol; ascorbic acid